Knowledge on adolescent and reproductive health among secondary school students in Khulna City, Bangladesh - Md. Shakilur Rahman; Kazi Abusaleh (Springer, 2024)
Abstract The main objective of this study was to investigate the depth and breadth of knowledge and ideas about adolescent health among secondary-level students. A concurrent mixed method approach, both quantitative and qualitative methods, was followed to carry out the study. Students enrolled in tenth grade under the Directorate of Secondary and Higher Education (DSHE) in Khulna City, Bangladesh, were chosen as the respondents of the study. Kotwali and Khanjahan Ali Thana of Khulna City were rationally chosen as the areas of the study. A total of 40 schools were randomly chosen, and 400 surveys, 10 surveys from each school, ideally 05 boys and 05 girls, were carried out, including 10 in-depth case studies. Findings indicated that, on average, more than half of the adolescents have knowledge gaps about adolescents and reproductive health, for example, misconceptions about the adolescent period and age range of puberty, vague understanding of the first sign(s) of physical appearances, and face critical emotional and social challenges. Both qualitative and quantitative data further showed that they hardly get sufficient cooperation and support from family and social environments in dealing with their challenges, display risky health behaviour, and make major decisions based on their self-discretionary assumptions to deal with crises. The findings of this study would provide important guidelines to parents and guardians, local and district and regional and national level GOs and NGOs health professionals who work with adolescent and reproductive health services, policymakers, academics, and researchers to create an adolescent-friendly environment.